DISKURSUS KEPERAWANAN DALAM INSTAGRAM (STUDI WACANA AKUN @agrimerinda) - Sani, Khosy Mawar (Paradigma, 2021)
Abstract The discourse that is scattered on social media raises various problems such as the discourse of virginity. The discourse of virginity that is rife on social media, especially Instagram, makes women as the other party feel disadvantaged, especially in the realm of a patriarchal society. The Instagram account @agrimerinda which was spearheaded by Agri Merinda dismissed the discourse on virginity and the negative stigma attached to non-virgin women and their sexual morality. The purpose of this study was to analyze the discourse on virginity on the @agrimerinda Instagram account. This study used a qualitative method with Michel Foucault’s archaeological and genealogical analysis. The results showed that the @agrimerinda account had the power to spread knowledge of sexuality and virginity massively and progressively across all Instagram features which were later agreed upon by its followers. The discourses presented by this account are related to virginity, including knowledge of sexuality (sex education), women’s sexual morality, myths and values of virginity. The discourses presented by Agri Merinda aim to change the taboo against nonvirgin women and make the narratives of sexuality and virginity a part of knowledge. Keyword: Discourse, Instagram, Virginity, Sexuality